Plastid genome variation in the green algal genus Coelastrum (Scenedesmaceae) - Lee, Chanhee; Jansen, Robert K.; Theriot, Edward C. (Frontiers in Plant Science, 2026)
Plastid genomes (plastomes) in green algae display remarkable variation in size and structure, yet comprehensive species and strain-level analyses remain rare. Here, we present a detailed plastome comparison across 29 strains of nine nominal species of the genus Coelastrum (Scenedesmaceae). Sizes ranged from 166,827 bp to 553,457 bp, the latter representing the largest plastomes reported to date in the order Sphaeropleales. An almost twofold size difference was observed between strains of the same species, Coelastrum morus, highlighting unprecedented intraspecific plastome expansion in closely related green algae. Comparative analyses revealed that plastome size variation is primarily driven by the expansion of non-coding regions and repeats accumulation, with additional contributions from inverted repeat (IR) length and intron contents. Phylogenomic inference based on shared protein-coding genes recovered well-supported clades and resolved species-level relationships, offering improved taxonomic resolution relative to previous analyses based on several single gene analyses (nuclear ITS, nuclear SSU, tufA) which provided different relationships among critical taxa in Coelastrum and Hariotina. However, uneven taxon and strain sampling among molecular phylogenetic studies of Coelastrum and closely related Scenedesmaceae, including ours, is possibly as much of an obstacle to resolution of incongruences as is gene sampling. While gene content was largely conserved, we documented several lineage-specific gene and tRNA losses and unique intron insertions, reflecting dynamic structural evolution. Our results provide new insights into plastome architecture, intron evolution, and species boundaries within Coelastrum, and demonstrate the value of dense taxon and strain sampling for understanding plastid genome evolution in Chlorophyta.